TRANSLATION PROCEDURES OF SIJALAPEN IN KARONESE WEDDING CEREMONY INTO ENGLISH - Milisi Sembiring; Martina Girsang (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2019)
The aims of this study were to observe the translation procedures to translate Sijalapen in Karonese Wedding Ceremony into English. The data of this study were found from the participant observation of the authors. There were six cultural terms in the groom’s party and five cultural terms in the bride’s party.  All together were 11 cultural terms and they were the lucky numbers for Karonese society. They refered to Karonese belief of ersada tendi ku rumah means have all souls gathered at home. If their souls are all at home, they believe that they all had good health. It was believed because they did the ceremony of perumah tendi. It was the ceremony of asking for their tendi at home. The qualitative research was done to collect the data and did the analysis. Translation analysis, cultural analysis and discourse analysis were applied in doing this study. The result shows that the problems of untranslatability occur in the process of translation the SL into the TL. Newmark’s translation procedures were not workable, instead, Sembiring and Panggabean’s familiar translation procedure were used to translate sijalapen in Karonese wedding ceremony into English. The authors would recommend the researchers on untranslatability texts to use Sembiring and Panggabean’s translation procedure to overcome their translation process problems.